PENGARUH MODEL DISCOVERY TERHADAP HASIL BELAJAR IPA KELAS V SDN SE-PONTIANAK KOTA - Liankim, Mentari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research to purpose the effect of discovery model on the learning result of natural science students class V SDN Pontianak city. This research method is experiment with quasi experimental design and research design nonequivalent control group design. The population of this research are 5 classes as many as 177 students. The sample in this research were 34 control class students and 36 experimental class students. Data collection techniques used in this study is a measurement technique, the instrument used is a form of test in the form of multiple choice with the amount of 50 questions. The research showed that the average post-test control class is 68.24 and the mean post-test experimental class is 78.77. The result of t- test got thitung 4,2391 amounted to 1,6693 and ttabel (α = 5% with dk = 68) that is meant thitung (4,2391) > ttabel (1,6693), so Ha is received. So, it can be concluded that there is effect discovery model of learning result of Natural Science Students class V SDN Pontianak City. The counting of effect size (ES), got ES amounted is 0,72 (high category). Keywords: Discovery Model, Learning Result